Social Study of Tourism Perceptions in Idaman Mangrove Ecotourism of Balang Baru Village, Tarowang District, Jeneponto Regency - Askar, Hardianty (Hasanuddin University, 2023)
This study aims to analyze the perceptions of visitors towards the existence of the Idaman Mangrove Ecotourism object. This research is a survey research using qualitative and quantitative approaches using questionnaire tools. This study was survey research by a qualitative and quantitative approach using a questionnaire tool. This research was done in Idaman Mangrove Ecotourism (IME) in Balang Baru Village, Tarowang District, Jeneponto Regency, South Sulawesi, Indonesia, from June to August 2020. The Non-physical aspects used the linear time function method for the tourists visiting IME. The number of visitor respondents was 40. The data were analyzed for social aspects towards perceptions of tourism using a Likert scale. The research results indicated that tourism perception belongs to the excellent category with 60%. The existence of mangrove ecotourism shows something unique and has a nature-based attraction, adequate facilities and infrastructure, and the comfort of activities that are good enough to meet the wishes of visitors.